2015
DOI: 10.2306/scienceasia1513-1874.2015.41.386
|View full text |Cite
|
Sign up to set email alerts
|

Iron and zinc variation along the grain length of different Thai rice varieties

Abstract: This study examined the distribution of iron (Fe) and zinc (Zn) along the grain length of seven rice varieties. The experiment was conducted in a completely randomized design with two factors (variety and grain fraction) and three independent replications. Samples of brown and white rice of six common Thai rice varieties and a high Fe and Zn variety, IR68144, were transversely cut into three fractions per grain (basal, middle, and distal) with approximately the same length in each fraction. The concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Similar results were reported earlier by Sridevi (2018) for zinc content in red and black coloured genotypes, compared to white rice genotypes. Pathak et al, (2017) and Laenoia et al, (2015) also reported that pigmented rice was found to have high amount of zinc content than non pigmented rice. Among the black pericarp genotypes, BPT 2848 (24.81ppm) recorded minimum zinc content, while BPT 3136 recorded maximum zinc content (30.16ppm).…”
Section: Resultsmentioning
confidence: 93%
“…Similar results were reported earlier by Sridevi (2018) for zinc content in red and black coloured genotypes, compared to white rice genotypes. Pathak et al, (2017) and Laenoia et al, (2015) also reported that pigmented rice was found to have high amount of zinc content than non pigmented rice. Among the black pericarp genotypes, BPT 2848 (24.81ppm) recorded minimum zinc content, while BPT 3136 recorded maximum zinc content (30.16ppm).…”
Section: Resultsmentioning
confidence: 93%
“…Belum dilakukan penelitian mengenai potensi kehilangan unsur Zn pada saat pengolahan gabah menjadi beras. Namun demikian, berdasarkan penelitian Laenoi et al (2015) proses penggilingan memengaruhi proses pendistribusi Zn dan Fe pada butir beras.…”
Section: Tantangan Pengembangan Varietas Ir Inpari Ir Nutri Zincunclassified